Cold-Sprayed TiO2 Coatings From Nanostructured Ceramic Agglomerated Powders - Abd Rahim, Toibah; Sato, Masahiro; Yamada, Motohiro; Fukumoto, Masahiro (Taylor & Francis Group, 2016)
In this work, synthesis of agglomerated TiO2, which is ready to be used after synthesis via a simple hydrolysis process, is described. The as-synthesized TiO2 powders were characterized by X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Field Emission Scanning Electron Microscope (FE-SEM), Transmission Electron Microscope (TEM) and DTA. DTA curve indicated that addition of (NH4)2SO4 into the starting precursor has accelerated the hydrolysis of titanyl sulfate. The XRD patterns showed that single-phase anatase TiO2 was produced using low-temperature hydrolysis at 80°C. SEM confirmed that the as-synthesized powders were in agglomerated form and in micro size. Addition of a structure-directing agent (SDA), (NH4)2SO4, promotes agglomeration, with a denser closed packing of particle arrangement, which reduces the number of existing porosities in the synthesized powder. The TEM image showed that the primary particles were nanoparticles. The preliminary study of coating formation depicted that the powder obtained could be used as the feedstock powder for the cold spray (CS) process to make the coating as it can be deposited onto the ceramic tile substrate.